Analisis Putusan Hakim Terhadap Anak Pelaku Tindak Pidana Ancaman Kejahatan Seksual (Putusan Pengadilan Negeri Semarapura Nomor: 2/Pid.Sus-Anak/2021/PN.Srp) - I Putu Agus Adi Pratama Yasa; A.A. Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2022)
The Indonesian state is a nation that has been separated from colonialism and has all kinds of freedoms but is believed to be still regulated by regulations. But in reality what is happening in the field is not the same and much different from the wishes of our country, one of which is the increasing number of crimes of sexual harassment. By using the normative method, two problem formulations were obtained, namely, the review of the panel of judges in giving a decision on acts of sexual abuse of children in criminal cases where the results of the judges' considerations stated that child sexual crimes could damage the future and honor of the victim. And the decision of the Semarapura District Court judge stated that it was definitely and rightly against the existing rules and the criminal act of threatening violence by coercion on a child to have intercourse with him. So it can be concluded that children's crimes are snared with a criminal which is expected to have a deterrent effect. The author's suggestion for the government, the community is to focus more on child protection.